Impact of transfer pricing methods for tax purposes on supply chain performance under demand uncertainty. (1st April 2013) - Huh, Woonghee Tim; Park, Kun Soo
Abstract Transfer pricing refers to the pricing of an intermediate product or service within a firm. This product or service is transferred between two divisions of the firm. Thus, transfer pricing is closely related to the allocation of profits in a supply chain. Motivated by the significant impact of transfer pricing methods for tax purposes on operational decisions and the corresponding profits of a supply chain, in this article, we study a decentralized supply chain of a multinational firm consisting of two divisions: a manufacturing division and a retail division. These two divisions are located in different countries under demand uncertainty. The retail division orders an intermediate product from the upstream manufacturing division and sets the retail price under random customer demand. The manufacturing division accepts or rejects the retail division's order. We specifically consider two commonly used transfer pricing methods for tax purposes: the cost‐plus method and the resale‐price method. We compare the supply chain profits under these two methods. Based on the newsvendor framework, our analysis shows that the cost‐plus method tends to allocate a higher percentage of profit to the retail division, whereas the resale‐price method tends to achieve a higher firm‐wide profit. However, as the variability of demand increases, our numerical study suggests that the firm‐wide and divisional profits tend to be higher under the cost‐plus method than they are under the resale‐price method. © 2013 Wiley Periodicals, Inc. Naval Research Logistics, 2013